PERBEDAAN PERANAN TINGKAT KEPUASAAN, KEPERCAYAAN DAN KOMITMEN PELANGGAN HOTEL: STUDI TENTANG SERVICE RELATIONSHIP PADA HOTEL DI JAKARTA DAN BOGOR - FARIDA JASFAR (Jurnal Bisnis dan Akuntansi, 2002)
This research aims to examine the difference behavioral intentions of hotel customers in Jakarta and Bogor. The differences in their feelings of satisfaction, trust and commitment are hypothesized to correlate with the service quality offered by hotels. It is hypothesized that significant associations exist between customer commitment and their trust, accumulative satisfaction and trust and between accumulative satisfaction and customer commitment. Differences in customer satisfaction, trust and commitment theoretically have an impact on their behavioral intentions and to their relationships pattern with the hotels they have visited. To clearly define the relationship pattern, customers are termed as being etiher temporal or loyal in their intentions. The degree of customer satisfaction, trust, commitment and service quality is measured according to the Likert scale, the comparative scale and the semantic scale and is based on completed valid questionnaires taken from 179 respondents (60% from 300 dispersed questionnaires). Based on average scores, the research findings conclude that there are significant differences in satisfaction, trust and commintment to a hotel service provider between loyal customers and temporal customers. Higher scores reflect the behavioral intentions of loyal customers whereas lower scores reflect the behavioral intentions of temporal customers.